Análise geomorfológica da Margem Continental Algarvia - Cunha, P. P. (2009)
The Algarve onshore, stretching out at the piedmont of the basement relieves (e.g. Serra do Caldeirão), documents a large planation surface cut on basement rocks and on the Mesozoic to Miocene sedimentary succession, associated with siliciclastic alluvial to coastal marine Pliocene deposits. Along the coast, Pleistocene terraces can be identified. From west to east, the coast exposes steep cliffs cut on the hard Carboniferous and Jurassic, then more sinuous ones on the softer lithologies of the Miocene and Pliocene, and finally a low sedimentary coast including the lagoon and barrier system of Faro region. The continental shelf comprises tectonic blocks showing at the top a wide planation surface covered by Pliocene and Pleistocene sediments. Marginal plateaux are separated by canyon heads or depressions enlarged by erosion along faults promoted by the Mediterranean bottom current. The plateaux are structural surfaces except in the areas where they have sediments deposited by contour currents.